PENGARUH MOTIVASI DAN KEMAMPUAN SURVEY TERHADAP KINERJA KARYAWAN STUDI KASUS PADA PT. TELKOM AKSES UNIT SURVEY DRAWING & DATA INVENTORY SEMARANG - Tita Putri Damayanti; Rodhiyah Rodhiyah (Jurnal Ilmu Administrasi Bisnis, 2017)
Every company want to have an optimal employee performance for accomplishing company’s goal. Performance of employees affected by several factors, such as motivation and capability. Therefore, PT Telkom Access committed to improve the performance of employees or company in order to achieve customer satisfaction. In fact, there are still many of the employees could not reach the survey target and high amount of absences. It can be indicated the low of motivation, survey capability, and employee’s performance.The aim of the study is showing the influence of motivation and survey capability to employees’ performance of PT Telkom Akses Unit Survey Drawing & Data Inventory Witel Semarang. The research type was using explanatory research, the research instrument is questionnaire. The population was not very big which 50 persons, so the method of the research was using saturated sample.The findings shows that motivation has influence to employees’ performance with 0,398 correlated coefficient and 15,9% determinate coefficient, survey capability has influence to employees’ performance with Y= 1,124+0,121 X1+0,576X2 equation. It meant that the higher motivation and survey capability of the employees, the higher performance. The conclusion of the research is both variables: motivation and survey capability have significant and positive influence to the employees’ performance. The findings suggested the firm to apply reward and punishment system, fix the work facility, review the payroll, and also increase the coordination of each related unit in order the survey can be done effectively.